Functional Programming - Simoni, Mary; Dannenberg, Roger B (Algorithmic Composition, 2013)
Functional programmingis a programming style that emphasizes the combination of functions to producevaluesas opposed to the sequential evaluation of commands and the modification ofvariables. One advantage of functional programming is that functional programs are often easier to reason about than non-functional alternatives. This chapter introduces some functional programming concepts and illustrates their use in computing scores. Lisp was one of the first languages to support functional programming, and by encouraging functional programming, Lisp has had a tremendous impact on many modern languages such as Java, Python, and ML. The main attraction of functional programming is that